First Report on Salvia Sahendica Boiss & Buhs roots biocomponents characterization by GC-MS and HPLC and Antibacterial Potency - Elnaz Nourozi; Ahad Hedayati; Mohammad Hossein Mirjalili; Hadi Madani; Atousa Aliahmadi; Ali Akbar Zahedi; Zahra Aslani (Scientific Reports, 2024)
Abstract Treatment of bacterial infections with antibiotic resistance is complicated. For this reason, new therapeutic methods are needed to control bacterial infections. Therefore, it is necessary to discover new antibiotics from medicinal plants that can destroy drug-resistant bacteria. Essential oils (EO) of some medicinal plants have antimicrobial effects and can be used as antimicrobial agents in the treatment of infections and food industries. The aim of this study was to determine the EO composition and antimicrobial effects of EO and polyphenols profile of Salvia Sahendica roots for the first time. Chemical compounds and antibacterial activity of EOs against Staphylococcus aureus and Bacillus cereus as gram-positive and Escherichia coli and Pseudomonas aeruginosa as gram- negative bacteria were evaluated using microtiter broth dilution method. Studied organs of S. sahendica showed significant diversity in terms of type and percentage of essential oil and polyphenol compounds. Overall, 44, 46, 42, and 45 compounds were identified in the essential oil of leaves, flowers, stems, and roots of this plant, which constituted 99.6, 99.3, 98.2, and 99.4% of total oil composition, respectively. The current study collectively demonstrated inhibitory effects ranged from strong (S. aureus) to low inhibition (P. aeruginosa). According to the HPLC result, the amounts of coumaric acid, chlorogenic acid, and gallic acid compounds in the root are higher than in other plant parts, which indicate that the root can be a suitable source for the production of these valuable polyphenol compounds. Due to the results, it is possible to hope for the application of EO from S. sahendica as natural antibacterial in the pharmaceutical and food industries.